Conditional Leptokurtosis in Energy Prices: Multivariate Evidence from Futures Markets - Massimiliano Marzo; Paolo Zagaglia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
We study the joint movements of the returns on futures for crude oil, heating oil and natural gas. We model the leptokurtic behavior through the multivariate GARCH with dynamic conditional correlations and elliptical distributions introduced by Pelagatti and Rondena (2004). Energy futures markets co-vary strongly. The correlation between the futures prices of natural gas and crude oil has been rising over the last 5 years. However, this correlation has been low on average over two thirds of the sample, indicating that futures markets have no established tradition of pricing natural gas as a function of developments on oil markets.
Keywords: 330; Ölpreis; Derivat; ARCH-Modell